Evaluation of Computerized Free Text Sign-Out Notes: Baseline Understanding and Recommendations - Campion, T.R. (Schattauer, 2010)
BACKGROUND: Standardization of sign-out, the transfer of patient information and responsibility between inpatient providers at shift change, is a Joint Commission National Patient Safety Goal intended to improve communication and reduce risk of error. Computerized systems with free text data entry and limited structure allow clinicians to generate sign-out notes in a variety of ways. OBJECTIVE: The literature lacks a systematic exploration of the range of content generated by users of computerized sign-out systems. The goal of this study was to determine if and how clinicians record standardized sign-out information using a system with free text data entry and limited structure. METHODS: Using qualitative methods, we reviewed free text sign-out notes for 730 patient cases across 39 hospital units at an academic medical center. RESULTS: Two categories of information expression emerged from analysis: patient treatment—comprised of patient summaries, awareness items, and action items—and care team coordination—consisting of discharge information, contact information, and social concerns. A third category describing the format of sign-out note content, presentation of information, also emerged. Location and structure of information varied, but sign-out note content for some hospital units exhibited specific characteristics and was relatively standardized. CONCLUSION: Findings provide a baseline understanding of computerized free text sign-out note content. Sign-out notes contained a synthesis of data from disparate sources. We recommend formalizing existing unit-specific content standardization and system use patterns to reduce sign-out note variability and improve communication.